Penerapan Analisis Biaya-Manfaat dalam Manajemen Pembiayaan Pendidikan - Teguh Trianung Djoko Susanto; Gelar Gelora Mestika; Ratih Kurnia Pasya; Neta Yolanda Putri; Suciko Violita (Journal of Research and Investigation in Education, 2025)
Education financing is a key element in ensuring the quality and sustainability of the teaching and learning process in educational institutions. In Indonesia, the management of the education budget still faces various problems, such as the imbalance in contributions between the government and the community, low transparency, and weak effectiveness in the use of funds. This study aims to analyze the application of the cost-benefit analysis (CBA) approach in educational institutions through a literature review of a number of relevant scientific articles. The study was conducted using a descriptive-qualitative approach to evaluate the extent to which education financing is managed efficiently and has an impact on the quality of education. The results of the study indicate that analysis methods such as CBA, Activity-Based Costing (ABC), and unit cost have begun to be applied in various educational contexts, but their implementation is not evenly distributed and still faces challenges in terms of data accuracy and financial accountability. In addition, there is a positive correlation between the level of education investment, both in terms of direct and indirect costs, and student academic achievement. This study concludes that education financing needs to be viewed as a long-term investment in human resource development, and not merely as a routine expenditure. Therefore, it is necessary to strengthen the managerial capacity of schools and the active involvement of stakeholders so that education budget management can be carried out more transparently, effectively, and based on real needs.